Application of the PBL Model with Vlog Media to Improve Critical Thinking Skills of Class III Students of SD Negeri Plumbon 04 Suruh District, Semarang Regency - Muhammad Habibie Zahrul Islam; Mawardi Mawardi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this Classroom Action Research is to improve critical thinking skills and learning outcomes. Theme 7 Sub-theme 4 for third grade students of SD Negeri Plumbon 04 Semester 2 of the 2021/2022 Academic Year, Suruh Sub-district, Semarang Regency through the Problem Based Learning learning model with Vloger Media. The researcher applied the Problem Based Learning learning model with Vloger Media to achieve these two things. This class action research was carried out in class III SD Negeri Plumbon 04 with a total of 9 students. Implementation time starts from April 18-24 to April 26 – May 1, 2022 or in the second semester of 2021/2022. From the research that has been carried out, the observations indicate that the average critical thinking skill reaches 12.3% with the learning outcomes of students who achieve mastery learning only reach 63% in cycle 1 In cycle 2 students' critical thinking skills increase to 14.7% with the learning mastery of students increased to 85 %. Based on the results of these studies, it can be concluded that the research conducted .experienced success. In other words, the application of the Problem Based Learning Model with Vloger Media can improve learning outcomes for Class III students at SD Negeri Plumbon 04, Suruh District, Semarang Regency.